Effect of different rolling schedules on the mechanical properties and microstructure of X60 type HSLA steel - Bakkaloglu, A (CARL HANSER VERLAG, 2001)
The application of microalloying, controlled rolling and controlled cooling has been the most important achievements in the metallurgical industry in the last 30 years. Microstructure and mechanical properties of steels are greatly improved by applying these technologies. This application resulted in significant progress in the production and application of high-strength low-alloy steel. In the present investigation, the effect of different lolling schedules on the microstructure and mechanical properties of grade X60 API steel has been studied. The tensile and impact properties of this steel are related to the microstructure introduced by various rolling schedules. It has been found that it is possible to obtain a steel with 25 % elongation to fracture, 560 MPa yield strength, 650 MPa tensile strength, and an impact transition temperature of -35 degreesC through thermomechanical rolling process.
Keywords: rolling schedules; mechanical properties of steel; microstructure of steel; steel X60 type HSLA; MICROALLOYED STEELS; CARBON; Metallurgy & Metallurgical Engineering